Simple and selective synthesis of 1-monolaurin without catalyst - CAYONA, RUEL (Archīum Ateneo, 2018)
Glycerol 1-monolaurate, also known popularly as 1-monolaurin, is a monoacylglycerol of lauric acid that has notable antimicrobial properties. It is present in abundant quantities is vegetable oils (i.e. coconut oil). Its most common route of preparation is from lauric acid and glycerol esterification involving chemical catalysts and enzymes. Unfortunately, this reaction is but a messy reaction which generates a mixture of glycerides that is difficult to purify. Significant effort was invested in the development of highly-selective catalysts but by far none is successful at producing 1-monolaurin exclusively as product. In this work, a simple and selective method of synthesis of 1-monolaurin is described that does not involve catalyst but activated reactants, instead. Lauric acid was first converted to lauroyl chloride before it was reacted with a sodium salt of an activated glycerol derivative, sodium glyceroxide. These reactants were allowed to react in a one-pot system and neat (no solvent) condition at room temperature and pressure. The reaction was both kinetically- and thermodynamically-favorable notwithstanding the modest conditions employed. This result was not achieved before with chemical catalysts or enzymes. The present yield may be low (3.41%) but optimization of relevant reaction variables could increase the yield of the target product and prepare the conditions for bulk synthesis. Furthermore, the method is a very promising alternative to high-purity 1-monolaurin preparation and potentially adaptable general procedure for 1-monoacylglycerides.